PENJAMINAN DANA NASABAH BANK OLEH LEMBAGA PENJAMIN SIMPANAN (Lex Journal: Kajian Hukum & Keadilan, 2019)
Liquidation and revocation of banking business licenses has caused public confidence in Indonesian banks to decline. Providing legal certainty in the regulation and supervision of banks and deposit guarantee is one way to increase public trust. The Deposit Insurance Agency is an independent institution that functions to guarantee the savings of banking customers in Indonesia. In this study using descriptive research methods with a normative legal approach. The results of this study indicate that the Indonesian people need security in guaranteeing their funds held in a bank. The goal is that customers increasingly put trust in banks and the more quantity of customers in using banking services. Customer funds guaranteed by the Deposit Insurance Corporation a maximum of Rp 2,000,000,000 (two billion rupiah), for customers whose savings are more than Rp 2,000,000,000 (two billion rupiah), or for customers whose deposits are not guaranteed, will be paid after disbursement of liquidated bank assets.Keywords:  Guarantee, Customer Funds, Deposit Insurance Corporation